The Transmission of Substrate Features: The case of Malacca Portuguese - Laub, Robert (Journal of Modern Languages, 2020)
Theories of the formation of creole syntax have been proposed to explain whether substrates and superstrates influence the resultant creole structures, and if so, what the mechanisms are by which they influence them. Using the framework of feature transfer, this study investigates features in Malacca Portuguese (MP), a Portuguese-based creole spoken in Malaysia. Citing grammatical characteristics such as aspect particles, I investigate similarities between features in MP and Malay, and how these similarities could have transferred from Malay to a Portuguese lexical item to create a grammatical words in MP. . I also discuss short/long variation in personal pronouns, as well as other features such as TAM markers and auxiliaries, and investigate how they have come about from a partial feature transfer from Malay. I propose that in this particular case a substrate has affected creole syntax, and provide evidence of how this has occurred. While a much more substantial exploration of this phenomenon is essential, I put forth a hypothesis about how the short/long distinction in pronouns functions in MP.